Multimedia multicast on the Internet (ISTE, 2007)
This book examines multicast technology and will be a key text for undergraduate engineering students and master students in networks and telecoms. However, it will be equally useful for a wide range of professionals in this research field. Multicast routing was introduced with the advent of multiparty applications (for example, videoconferencing on the Internet) and collaborative work (for example, distributed simulations). It is related to the concept of group communication, a technique introduced to reduce communication costs. The various problems of multicast routing on the Internet are examined in detail. They include: group membership management, quality of service, reliability, safety, scalability and transport. Throughout the text, several protocols are introduced in order to analyze, compare and cover the various aspects of multicast routing